Using a medium-throughput comet assay to evaluate the global DNA methylation status of single cells - Lewies, Angélique; Van Dyk, Etresia; Wentzel, Johannes F.; Pretorius, Pieter J. (Frontiers in Genetics, 2014)
The comet assay is a simple and cost effective technique, commonly used to analyse and quantify DNA damage in individual cells. The versatility of the comet assay allows introduction of various modifications to the basic technique. The difference in the methylation sensitivity of the isoschizomeric restriction enzymes HpaII and MspI are used to demonstrate the ability of the comet assay to measure the global DNA methylation level of individual cells when using cell cultures. In the experiments described here, a medium-throughput comet assay and methylation sensitive comet assay are combined to produce a methylation sensitive medium-throughput comet assay to measure changes in the global DNA methylation pattern in individual cells under various growth conditions.